The CDC biofilm bioreactor is a suitable method to grow biofilms, and test their sanitiser susceptibilities, in the dairy context. (March 2022) - Lindsay, D.; Killington, A.; Fouhy, K.; Loh, M.; Malakar, P.
Abstract: This study evaluated the CDC biofilm bioreactor as a suitable tool for growing biofilms of dairy pathogens within a dairy matrix, and then subsequently testing these biofilms for their susceptibilities to sanitisers used in dairy manufacturing environments. An effective sanitiser reduces the attached population by ≥3 log cfu. The numbers of bacterial cells (∼4.5 log cfu cm −2 Cronobacter and Listeria monocytogenes ; and ∼5 log cfu cm −2 Salmonella and Staphylococcus aureus ) that attached to stainless steel surfaces in the CDC reactor were high enough to allow for the observation of ≥3 log reduction during sanitiser treatments. Isopropanol was more effective than ethanol, and concentrations of inactivation correlated with known literature values. Only five of the eight commercial sanitisers tested were considered effective (≥3 log reduction). The CDC reactor was a suitable method to grow dairy biofilms for subsequent sanitiser efficacy testing.